Has the Targeted Poverty Alleviation program improved household welfare in rural China? - Chang, Qing (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2022)
China's government launched the Targeted Poverty Alleviation (TPA) program in 2015 as a part of a multipronged framework to lift every Chinese above the national poverty line by 2020. This study is devoted to examining the effects of the TPA program on household welfare indicators. To this end, the China Family Panel Studies data for the period 2010–2018 are analyzed. The propensity score matching and difference-in-difference (PSM-DID) method is employed to address the sample selection bias and endogeneity inherent in program participation. The results show that TPA program participants earn significantly higher incomes than non-participants. However, the program's effect on consumption expenditure is insignificant, suggesting that the program has contributed to lifting people out of poverty mainly by increasing incomes. Furthermore, even though the program seeks to deliver precisely targeted interventions, it is more effective in some regions than in others. Removing regional disparities is an area of opportunity for improving the efficacy of the TPA program.